Political, Economic, and Social Determinants of China’s Belt and Road Initiative’s Reception as A Soft Power Strategy - Ekoko, Esther Victoria; Orhero, A. E.; Ikeng, Francis A. (Universitas Indonesia Mandiri, 2025)
China’s Belt and Road Initiative (BRI) has emerged as a transformative global infrastructure and development project since its launch in 2013. Beyond its economic scope, the initiative is increasingly framed as a strategic vehicle of China’s soft power. However, the reception and interpretation of the BRI vary across regions, influenced by political, economic, and social conditions. This paper investigates the contextual factors shaping perceptions of the BRI in Asia, Latin America, and Africa, using a discursive analytical approach. Findings highlight the importance of local political legitimacy, economic sustainability, and social narratives in mediating China’s influence and underscore the conditional nature of soft power.